IL-35-producing B cells in gastric cancer patients. Issue 19 (May 2018) - Wang, Ke; Liu, Jianming; Li, Jiansheng
Abstract : Abstract: A significant characteristic of advanced gastric cancer (GC) is immune suppression, which can promote the progression of GC. Interleukin 35 (IL-35) is an immune-suppressing cytokine, and it is generally recognized that this cytokine is secreted by regulatory T (Treg) cells. Recently, studies have found that IL-35 can also be produced by B cells in mice. However, scientific studies reporting that IL-35 is secreted by B cells in humans, specifically in cancer patients, are very rare. Blood samples were collected from 30 healthy controls (HCs) and 50 untreated GC patients, and IL-35-producing B cells in the peripheral blood were investigated. Moreover, Treg cells (CD4 + CD25 high/+ CD127 low/− ), myeloid-derived suppressor cells (MDSCs) (CD14 + HLA-DR low/− ) and other lymphocyte subsets (CD3 +, CD4 +, CD8 + T cells, activated and memory CD4 + T cells, activated CD8 + T cells, CD14 + monocytes, and IL-10-producing B cells) were also examined. IL-35-producing B cells were significantly upregulated in patients with advanced GC. Furthermore, the frequency of IL-35-producing B cells was positively correlated with the frequencies of Treg cells (CD4 + CD25 high/+ CD127 low/− ), MDSCs (CD14 + HLA-DR low/− ), IL-10-producing B cells, and CD14 + monocytes in these GC patients. In summary, the frequency of IL-35-producing B cells is significantly elevated in advanced GC; this outcome implies that this group of B cells may participate in GC progression.